The Prevalence Overexpression Of C-Erbb-2 Oncoprotein In Carcinoma Of The Prostate-Mulago Hospital - Alenyo, R.; Odida, M.; Watya, S. (East and Central African Journal of Surgery, 2008)
Over expression of C-erbB-2 a Human epidermal growth factor has been reported in several human carcinomas including prostate cancer. In prostate cancer studies have for it to have a prognostic role and to predict likelihood of resistance in hormonal therapy. The oncoprotein receptors are now being looked at as possibility of prognostic predictor at the same time as a target for therapy in cancers.
Keywords: C-Erbb-2; oncoprotein; carcinoma; Prostate